Redefinition of "Network learning" in the fourth industrial revolution - Alexandro Escudero Nahón (Universidad de Guadalajara, 2018)
The "fourth industrial revolution" will provoke a transformation in educational scenarios because it will incorporate cyber-physical networks in the production, logistics and consumption of goods and services. Educational theory has traditionally approached technological educational scenarios with categories of analysis typical of the third industrial revolution and it is necessary to overcome these conceptual weights. This paper proposes the concept of "network learning" taking as a starting point the posthumanist ontology and the epistemology of the actor-network theory. Thus, learning would be a process that associates human and non-human agencies alike, which operates without center nor periphery, and whose objective is to guarantee self-regulation and persistence because as soon as the agencies stop operating, the learning network disappears. Learning is, in itself, a heterogeneous network in operation. Likewise, this paper identifies some basic human and non-human agencies that allow learning networks to be established, strengthened or destroyed. In addition, it is justified why educational research should create data through an inductive manner and construct categories of analysis abductively to identify new objects of study in the learning scenarios of the fourth industrial revolution, which are characterized by being hybrid, ambiguous and contingent.